Formation and fragmentation of protonated molecules after ionization of molecular clusters with multiply charged ions. (August 2015) - Vizcaino, V; Poully, J-C; Schwob, L; Delaunay, R; Kočišek, J; Eden, S; Chesnel, J-Y; Méry, A; Rangama, J; Adoui, L; Huber, B
Synopsis: Collisions between neutral clusters of biomolecules (amino-acids and lactic acid) and keV ions in the gas-phase lead, in very large majority, to protonated species. We found that the target proton affinity and the nature of the projectile ion influence the protonation of monomers within these clusters. New fragment ion channels were also observed and have been assigned to the statistical dissociation of these protonated molecules formed upon ionization of the clusters. These new dissociation channels exhibit strong delayed fragmentation in the μs time scale.